Determination of absolute O(3P) and O2(a1Δg) densities and kinetics in fully modulated O2 dc glow discharges from the O2(X3Σg−) afterglow recovery dynamics. (11th November 2020) - Booth, J-P; Chatterjee, A; Guaitella, O; Sousa, J Santos; Lopaev, D; Zyryanov, S; Rakhimova, T; Voloshin, D; Mankelevich, Yu; de Oliveira, N; Nahon, L
Abstract: A method is presented for the determination of the absolute densities of O( 3 P) atoms and O2 (a 1 Δg ) molecules in an O2 electrical discharge, which does not depend on any calibration procedure or knowledge of optical transition strengths. It is based on observing the recovery dynamics of the O2 (X 3 Σg − ) density in the afterglow of a fully-modulated discharge, and is demonstrated in a dc glow discharge in pure О2 at pressures of 0.2–4 Torr. The time-resolved O2 (X 3 Σg − ) density was measured by VUV absorption spectroscopy using the monochromator branch of the VUV DESIRS beamline at Synchrotron SOLEIL, but this methodology could be used with another density measurement technique. During the active discharge, the O2 (X 3 Σg − ) density is depleted by a combination of О2 dissociation, excitation into metastable states (principally O2 (a 1 Δg )) and gas heating/dilation. After discharge extinction, the O2 (X 3 Σg − ) density progressively recovers to its initial (before discharge) value, with three distinct time-constants due to: (i) gas cooling (fast), (ii) O( 3 P) atom recombination (intermediate), and (iii) O2 (a 1 Δg ) quenching (slow). The O( 3 P) and O2 (a 1 Δg ) dynamics can be separated easily, allowing the O( 3 P) and O2 (a 1 Δg ) afterglow loss kinetics to be determined, as well as their mole fractions in the steady-state discharge. Both the O( 3 P) and O2 (a 1 Δg ) mole-fractions increase with current (up to the highest current studied, 40 mA) and pass through maxima with pressure at 1 Torr, reaching 16.5% and 8%, respectively. O( 3 P) atoms are principally lost by recombination at the borosilicate tube surface, with a loss probability in the afterglow of ∼8 × 10 −4, nearly independent of gas pressure and discharge current (in contrast to previous observations in the active discharge [1 ]). The O2 (a 1 Δg ) dynamics were also measured by IR emission spectroscopy. In the late afterglow, this agrees well with the O2 (X 3 Σg − ) recovery dynamics, corresponding to an O2 (a 1 Δg ) surface loss probability of ∼2.2 × 10 −4 . The initial O2 (a 1 Δg ) loss is faster than in the later afterglow, indicating that it is also quenched by O atoms.